Low-temperature self-curing organic silicon ultraviolet light conversion coating, preparation method thereof and photovoltaic module
By introducing low-temperature self-curing silicone ultraviolet conversion coatings into the coating formula of perovskite batteries, the stability problem of perovskite batteries under ultraviolet light is solved, the barrier and conversion of ultraviolet light is realized, the power generation performance is improved, and the external cleaning frequency and heat dissipation efficiency of the battery are improved through hydrophobicity and thermal conductivity.
Patent Information
- Application Number
- CN202510063971.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The stability of perovskite batteries under ultraviolet light irradiation limits their practical application, especially the packaging materials are unstable to ultraviolet light and the electron transport layer and hole transport layer on the surface of the battery are ultraviolet-sensitive materials, resulting in discoloration, aging and a decrease in power generation.
The low-temperature self-curing silicone ultraviolet conversion coating is used to prepare silicone hydrophobic coating by mixing silicone resin, diluent, defoaming agent and leveling agent, and mixing it with the ultraviolet conversion dispersion to form a low-temperature self-curing silicone ultraviolet conversion coating, which is applied to the battery surface to achieve ultraviolet barrier and light stability.
This technology improves the power generation performance of perovskite batteries by introducing ultraviolet conversion components into the coating formula, improving the power generation performance of perovskite batteries; the silicone system makes the coating surface oleophobic and hydrophobic, reducing the frequency of dust cleaning; the addition of nano-thermal conductive materials promotes the heat dissipation rate, ensuring the efficient and stable operation of the battery under ultraviolet.
Smart Images

Figure BDA0005243695990000091 
Figure BDA0005243695990000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite cells, and specifically relates to a low-temperature self-curing organosilicon ultraviolet light-conversion coating and a preparation method thereof, and a photovoltaic module. Background Art
[0002] As a new type of organic photovoltaic product, perovskite cells have many advantages such as high conversion efficiency, low manufacturing cost, and wide application range. At present, perovskite stacked cells, including perovskite stacked heterojunction / perovskite stacked Topcon, have become an important development direction for leading companies. Perovskite stacked cells will have a better market prospect. As of the end of 2023, more than 10,000 papers have been published in the field of perovskite photovoltaic cells, with multiple research directions. Some domestic perovskite battery companies have also gradually achieved GW-level production line shipments, and perovskite batteries are also considered to be the technology with the most potential to compete with silicon-based solar cells in the future.
[0003] However, the stability issues of perovskite materials under ultraviolet light limit their practical applications.
[0004] Perovskite cells are currently generally encapsulated with acid-free resins such as POE or TPO to prevent the resin from releasing acidic substances during the aging process, which may corrode the perovskite material and reduce the battery performance. The encapsulation method mostly adopts the encapsulation solution of ITO conductive glass + encapsulation film + back glass. The perovskite cell is coated on the inner surface of the ITO conductive glass by surface coating, so it is impossible to block UV rays through the encapsulation material.
[0005] At the same time, the electron transport layer and hole transport layer on the surface of the perovskite battery are currently UV-sensitive materials, which are prone to discoloration and aging under long-term UV irradiation, thereby causing a significant drop in the battery's power generation capacity.
[0006] Therefore, how to overcome the defect that the packaging materials of perovskite cells are unstable to ultraviolet light is a technical problem that needs to be solved urgently in this field.
[0007] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0008] The embodiments of the present disclosure at least provide a low-temperature self-curing organosilicon ultraviolet light-conversion coating and a preparation method thereof, and a photovoltaic module.
[0009] In a first aspect, an embodiment of the present disclosure provides a method for preparing a low-temperature self-curing silicone ultraviolet light-conversion coating, comprising the following steps: step S1, preparing a silicone hydrophobic coating, namely, mixing a silicone resin and a diluent, increasing the speed of shearing until they are completely dispersed, adding a defoaming agent and a leveling agent in sequence, and reducing the speed of mixing to obtain a silicone hydrophobic coating; step S2, preparing an ultraviolet light-conversion dispersion, namely, mixing an organic solvent, an ultraviolet light-conversion agent and a light stabilizer, heating and stirring until they are completely dissolved, slowly adding a nano-thermal conductive material, stirring and increasing the speed until they are completely dispersed to form a uniform suspension, and obtaining an ultraviolet light-conversion dispersion; step S3, uniformly mixing the silicone hydrophobic coating and the ultraviolet light-conversion dispersion in a mass ratio of (90-99): (1-10), and applying the mixture on the surface of a battery to form a low-temperature self-curing silicone ultraviolet light-conversion coating.
[0010] In an optional embodiment, the silicone resin includes any one or more combinations of methylphenyl silicone resin, methyl silicone resin, low phenylmethyl silicone resin, epoxy-modified silicone resin, silicone polyester modified resin, benzyl transparent silicone resin, methyl transparent silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone polyester resin, methyl MQ silicone resin and vinyl MQ silicone resin.
[0011] In an optional embodiment, the diluent includes tetraethyl orthosilicate and isopropyl alcohol mixed in a mass ratio of (6-8):(2-4).
[0012] In an optional embodiment, the defoaming agent is a silicone defoaming agent, preferably DF-601, HY-024, AFE-3168, KS-66, KSZ-108, KM-7752.
[0013] In an optional embodiment, the leveling agent includes any one of BYK series, MOK series, 450W, 411, 415, 485, A115, and 2300.
[0014] In an optional embodiment, the mass fractions of the components in step S1 are: 100 parts of silicone resin, 10-30 parts of diluent, 0.1-0.3 parts of defoaming agent, and 0.2-0.7 parts of leveling agent.
[0015] In an optional embodiment, the organic solvent includes pentaerythritol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetraacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane trimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate. Ester, ethylene glycol dimethacrylate, polyethylene glycol (200) diacrylate, polyethylene glycol (400) diacrylate, polyethylene glycol (600) diacrylate, polyethylene glycol (200) dimethacrylate, polyethylene glycol (400) dimethacrylate, polyethylene glycol (600) dimethacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, and any one or more combinations of neopentyl glycol diacrylate.
[0016] In an optional embodiment, the light conversion agent includes any one or more combinations of light conversion agents having any one of benzothiazolyl, benzoxazinyl, quinazoline, quinolyl, isoquinolyl, quinoxalinyl, pyridyl, pyridazinyl, pyrimidinyl, pyrazinylpyrrolyl as the parent.
[0017] In an optional embodiment, the light stabilizer is a hindered amine light stabilizer, including any one or more combinations of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, mono(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) sebacate.
[0018] In an optional embodiment, the nano thermal conductive material includes any one or more combinations of boron nitride, aluminum nitride, silicon nitride, copper oxide, zinc oxide, ATO conductive powder, carbon fiber, single-layer graphene sheet, carbon nanotube, and aluminum oxide.
[0019] In a second aspect, the embodiments of the present disclosure further provide a low-temperature self-curing organosilicon ultraviolet light-conversion coating, which is prepared by the method described above, and the thickness of the low-temperature self-curing organosilicon ultraviolet light-conversion coating is 20 to 100 μm.
[0020] In a third aspect, the embodiments of the present disclosure further provide a photovoltaic module, including a perovskite cell; wherein the outer glass surface of the perovskite cell is provided with a low-temperature self-curing silicone ultraviolet light-conversion coating as described above.
[0021] The beneficial effects of the present invention are that the low-temperature self-curing silicone ultraviolet light-conversion coating and its preparation method, and the photovoltaic module introduce ultraviolet light-conversion components into the existing coating formula to convert ultraviolet light into visible light under the premise of achieving ultraviolet blocking, thereby improving the power generation performance of the module; at the same time, the silicone system makes the coating surface oleophobic and hydrophobic, reducing the frequency of cleaning dust on the surface of the module for long-term outdoor power generation; in addition, the addition of nano-thermal conductive materials also promotes the heat dissipation rate of the module, jointly ensuring the efficient and stable operation of the perovskite battery module under ultraviolet light.
[0022] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description.
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below for detailed description as follows. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0026] In this document, as used herein, expressions such as "at least one of..." when following a list of elements modify the entire list of elements rather than modifying the individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0027] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0028] In this article, for example, polyethylene glycol (200) diacrylate refers to an average molecular weight of 200, and other similar expressions refer to the molecular weight of the chemical formula.
[0029] Some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0030] The embodiment of the present disclosure provides a method for preparing a low-temperature self-curing organic silicon ultraviolet light-conversion coating, comprising the following steps: step S1, preparing an organic silicon hydrophobic coating, namely, mixing a silicone resin and a diluent, increasing the speed of shearing until they are completely dispersed, adding a defoaming agent and a leveling agent in sequence, and reducing the speed of mixing for 1-2 hours to obtain an organic silicon hydrophobic coating; step S2, preparing an ultraviolet light-conversion dispersion, namely, mixing an organic solvent, an ultraviolet light-conversion agent and a light stabilizer, heating and stirring until they are completely dissolved, slowly adding a nano thermal conductive material, stirring and increasing the speed until they are completely dispersed to form a uniform suspension, and obtaining an ultraviolet light-conversion dispersion; step S3, uniformly mixing the organic silicon hydrophobic coating and the ultraviolet light-conversion dispersion in a mass ratio of (90-99):(1-10), and applying the mixture on the surface of a battery to form a low-temperature self-curing organic silicon ultraviolet light-conversion coating.
[0031] In some embodiments, specifically, the silicone resin includes any one or more combinations of methylphenyl silicone resin, methyl silicone resin, low phenylmethyl silicone resin, epoxy-modified silicone resin, silicone polyester-modified resin, benzyl transparent silicone resin, methyl transparent silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, methyl MQ silicone resin and vinyl MQ silicone resin.
[0032] In some embodiments, specifically, the diluent includes ethyl orthosilicate and isopropyl alcohol mixed in a mass ratio of (6-8):(2-4), preferably 7:3.
[0033] In some embodiments, specifically, the defoaming agent is a silicone defoaming agent, preferably DF-601, HY-024, AFE-3168, KS-66, KSZ-108, KM-7752.
[0034] In some embodiments, specifically, the leveling agent includes any one of BYK series, MOK series, and 450W, 411, 415, 485, A115, and 2300.
[0035] In some embodiments, specifically, the mass fractions of the components in step S1 are: 100 parts of silicone resin, 10-30 parts of diluent, 0.1-0.3 parts of defoaming agent, and 0.2-0.7 parts of leveling agent.
[0036] In some embodiments, specifically, the organic solvent includes pentaerythritol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetraacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane trimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate. Ester, ethylene glycol dimethacrylate, polyethylene glycol (200) diacrylate, polyethylene glycol (400) diacrylate, polyethylene glycol (600) diacrylate, polyethylene glycol (200) dimethacrylate, polyethylene glycol (400) dimethacrylate, polyethylene glycol (600) dimethacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, and any one or more combinations of neopentyl glycol diacrylate.
[0037] In some embodiments, specifically, the light conversion agent includes any one or more combinations of light conversion agents having any one of benzothiazolyl, benzoxazinyl, quinazoline, quinolyl, isoquinolyl, quinoxalinyl, pyridyl, pyridazinyl, pyrimidinyl, pyrazinyl, and pyrrolyl as the parent.
[0038] In some embodiments, specifically, the light stabilizer is a hindered amine light stabilizer, including any one or more combinations of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, mono(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) sebacate.
[0039] In some embodiments, specifically, the nano thermal conductive material includes any one or more combinations of boron nitride, aluminum nitride, silicon nitride, copper oxide, zinc oxide, ATO conductive powder, carbon fiber, single-layer graphene sheet, carbon nanotube, and aluminum oxide.
[0040] The disclosed embodiment also provides a low-temperature self-curing organosilicon ultraviolet light-conversion coating, which is prepared by the method described above, and the thickness of the low-temperature self-curing organosilicon ultraviolet light-conversion coating is 20 to 100 μm.
[0041] The disclosed embodiment also provides a photovoltaic module, including a perovskite cell; wherein the outer glass surface of the perovskite cell is provided with the low-temperature self-curing silicone ultraviolet light-conversion coating as described above.
[0042] Example 1
[0043] A method for preparing a low-temperature self-curing organosilicon ultraviolet light-converting coating comprises the following steps:
[0044] Step S1, preparing an organosilicon hydrophobic coating, that is, mixing a silicone resin and a diluent, increasing the speed to 800-1000r / min and shearing until completely dispersed, adding a defoamer and a leveling agent in sequence, reducing the speed to 300-500r / min and mixing for 1h to obtain an organosilicon hydrophobic coating;
[0045] The diluent is ethyl orthosilicate and isopropyl alcohol in a mass ratio of 7:3;
[0046] Step S2, preparing a UV light conversion dispersion, that is, mixing an organic solvent, a UV light conversion agent and a light stabilizer, heating to 70° C. and stirring until completely dissolved, slowly adding the nano thermal conductive material, stirring at an increased speed until completely dispersed to form a uniform suspension, and obtaining a UV light conversion dispersion;
[0047] Step S3, mixing the organic silicon hydrophobic coating and the ultraviolet light conversion dispersion evenly, and applying the mixture on the surface of the battery to form a low-temperature self-curing organic silicon ultraviolet light conversion coating.
[0048] According to the method of Example 1, Examples 1-9 and Comparative Examples 1-3 were prepared, and the component ratios and performance data are shown in Table 1 below.
[0049] Test method:
[0050] Water contact angle test method:
[0051] The coating is applied on the glass surface, and the coating thickness is controlled to be 20-100 μm. After curing, the water contact angle is tested according to GB / T30693-2014.
[0052] Module power gain test method:
[0053] Refer to IEC61215 test method
[0054] 1. First, prepare the solar cells and conventional films (commercially available conventional EVA / EPE / POE films, the performance of which meets the GB / T29848-2013 standard) into photovoltaic modules according to standard components, and keep the prepared photovoltaic modules in a 25℃ room for one day to ensure that the surface temperature of the modules is 25±1℃. First, calibrate the power tester with a standard plate, then test the initial power of the prepared modules and record it. The average value of the three tests is taken as the initial power generation power of the sample, which is Pmax1.
[0055] 2. Apply the light-conversion coating evenly on the surface of the photovoltaic module with a thickness of 20 to 100 μm, and keep the prepared photovoltaic module in a room at 25°C for one day to ensure that the surface temperature of the module is 25±1°C. First, calibrate the power tester with a standard plate, then test the initial power of the prepared module and record it. Test three times and take the average value as the initial power generation power of the sample, which is Pmax2.
[0056] Module power gain = Pmax2-Pmax1
[0057] Thermal conductivity test:
[0058] Place the coated photovoltaic glass on the surface of a constant temperature heating table, set the temperature of the heating table to 45°C, heat it at a constant temperature for 5 minutes, then remove it and cool it for 1 minute. Test the temperature on the back of the photovoltaic glass to evaluate the heat dissipation performance of the coating.
[0059] UV500h power attenuation:
[0060] Refer to IEC61215, 1. First, prepare the solar cells and conventional films (commercially available conventional EVA / EPE / POE films, the performance of which meets the GB / T29848-2013 standard) into photovoltaic modules according to standard modules, and evenly coat the light-converting coating on the surface of the photovoltaic modules with a thickness of 20-100μm, and keep the prepared photovoltaic modules in a 25℃ room for one day to ensure that the surface temperature of the modules is 25±1℃. First, calibrate the power tester with a standard board, then test the initial power of the prepared modules and record it. The average value of the three tests is taken as the initial power generation power of the sample, which is Pmax1.
[0061] 2. Place the prepared components in a UV aging box and set the aging time to 500h. After aging, take out the components and keep them in a 25℃ room for one day to ensure that the surface temperature of the components is 25±1℃. First, calibrate the power tester with a standard board, then test the initial power of the prepared components and record it. Test three times and take the average value as the initial power generation power of the sample, which is Pmax2.
[0062] UV500h=(Pmax2-Pmax1) / Pmax1
[0063] Table 1
[0064]
[0065]
[0066] It can be seen from Table 1 that in Comparative Example 1, when no light conversion agent is added, the power attenuation and power gain of the photovoltaic module are both poor, which is also the main problem faced by perovskite cell photovoltaic modules; in Comparative Example 2, when no thermal conductive material is added, due to the poor heat dissipation effect, although the gain efficiency of the module is not greatly affected, the power attenuation is obvious in the UV500h test; in Comparative Example 3, when no light stabilizer is added, even with the addition of thermal conductive material, the heat dissipation of the module is still poor, and at the same time, due to the absence of light stabilizer, the power attenuation of the module is more obvious.
[0067] In summary, the low-temperature self-curing silicone UV conversion coating and its preparation method, and photovoltaic modules introduce UV conversion components into the existing coating formula to convert UV light into visible light while achieving UV blocking, thereby improving the power generation performance of the module; at the same time, the silicone system makes the coating surface oleophobic and hydrophobic, reducing the frequency of cleaning dust on the surface of the module for long-term outdoor power generation; in addition, the addition of nano-thermal conductive materials also promotes the heat dissipation rate of the module, jointly ensuring the efficient and stable operation of the perovskite battery module under UV light.
[0068] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a low-temperature self-curing organosilicon ultraviolet light-conversion coating, characterized in that: The steps include: Step S1, preparing a silicone hydrophobic coating, That is, after the silicone resin and the diluent are mixed, the speed is increased and sheared until they are completely dispersed, a defoamer and a leveling agent are added in sequence, and the speed is reduced and mixed to obtain a silicone hydrophobic coating; Step S2, preparing a UV light conversion dispersion, That is, after mixing the organic solvent, the ultraviolet light conversion agent and the light stabilizer, heating and stirring until they are completely dissolved, slowly adding the nano thermal conductive material, stirring and speeding up until they are completely dispersed to form a uniform suspension state, and obtaining the ultraviolet light conversion dispersion; Step S3, mixing the organic silicon hydrophobic coating and the ultraviolet light conversion dispersion in a mass ratio of (90-99): (1-10) evenly, and applying the mixture on the surface of the battery to form a low-temperature self-curing organic silicon ultraviolet light conversion coating.
2. The preparation method according to claim 1, characterized in that The silicone resin includes any one or more combinations of methylphenyl silicone resin, methyl silicone resin, low phenylmethyl silicone resin, epoxy-modified silicone resin, silicone polyester modified resin, benzyl transparent silicone resin, methyl transparent silicone resin, polymethyl silicone resin, amino silicone resin, fluorosilicone resin, silicone polyester resin, methyl MQ silicone resin and vinyl MQ silicone resin.
3. The preparation method according to claim 1, characterized in that: The diluent includes ethyl orthosilicate and isopropyl alcohol mixed in a mass ratio of (6-8):(2-4).
4. The preparation method according to claim 1, characterized in that: The mass fractions of each component in step S1 are: 100 parts of silicone resin, 10-30 parts of diluent, 0.1-0.3 parts of defoaming agent, and 0.2-0.7 parts of leveling agent.
5. The preparation method according to claim 1, characterized in that: The organic solvent includes pentaerythritol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetraacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane trimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate A combination of any one or more of methacrylate, polyethylene glycol (200) diacrylate, polyethylene glycol (400) diacrylate, polyethylene glycol (600) diacrylate, polyethylene glycol (200) dimethacrylate, polyethylene glycol (400) dimethacrylate, polyethylene glycol (600) dimethacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, and neopentyl glycol diacrylate.
6. The preparation method according to claim 1, characterized in that: The light conversion agent includes any one or more combinations of light conversion agents with any one of benzothiazolyl, benzoxazinyl, quinazoline, quinolyl, isoquinolyl, quinoxalinyl, pyridyl, pyridazinyl, pyrimidinyl, pyrazinylpyrrolyl as the parent.
7. The preparation method according to claim 1, characterized in that: The light stabilizer is a hindered amine light stabilizer, including any one or more combinations of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, mono(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate.
8. The preparation method according to claim 1, characterized in that: The nano thermal conductive material includes any one or more combinations of boron nitride, aluminum nitride, silicon nitride, copper oxide, zinc oxide, ATO conductive powder, carbon fiber, single-layer graphene sheet, carbon nanotube, and aluminum oxide.
9. A low-temperature self-curing organosilicon ultraviolet light-converting coating, characterized in that: The low-temperature self-curing organic silicon ultraviolet light-conversion coating is prepared by the method according to any one of claims 1 to 8, and the thickness of the low-temperature self-curing organic silicon ultraviolet light-conversion coating is 20 to 100 μm.
10. A photovoltaic module, characterized in that: Including perovskite cells; The outer glass surface of the perovskite cell is provided with the low-temperature self-curing silicone ultraviolet light-conversion coating as claimed in claim 9.